The Utilization of Learning Media to Improve the Quality of Education at SDN Samadua, South Aceh - silfia andriani; Rahmattullah; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the utilization of learning media to enhance the quality of education at SDN Samadua in South Aceh. In the context of educational reform and the increasing integration of technology in teaching, this research aims to identify effective strategies for incorporating diverse learning media into the curriculum. The study involves qualitative and quantitative methods, including surveys and interviews with teachers, students, and parents, to assess the current state of learning media usage in the school. Key findings reveal that incorporating digital tools, visual aids, and hands-on activities significantly improves student engagement and comprehension, fostering a more dynamic learning environment. Furthermore, the study emphasizes the importance of training teachers in the effective use of these media and the value of parental involvement in the educational process. By promoting collaborative learning and leveraging local resources, the school can enhance its educational offerings. The implications of this research underscore the need for ongoing professional development for educators and a supportive infrastructure that facilitates the integration of innovative learning media. The ultimate goal is to create an interactive and effective educational environment that enhances student learning outcomes and contributes to the overall improvement of educational quality at SDN Samadua.